Intuitionistic Fuzzy N-Compactness by Intuitionistic Fuzzy Nets. (3rd March 2016) - Pankajam, N.; Pushpalatha, A.
Abstract: In this paper, we introduce the notion of R-neighbourhood of an intuitionistic fuzzy point to investigate the compactness by intuitionistic fuzzy nets for arbitrary intuitionistic fuzzy sets and we discuss a series of properties.